Optimalisasi AI Dalam Digital Marketing UMKM Pariwisata - Yogi Putra; Furqan (Journal of Trends Economics and Accounting Research, 2025)
This research aims to analyse the optimisation of Artificial Intelligence (AI) in digital marketing strategies to support the development of tourism MSMEs in Sugihen Village in the Society 5.0 era. The background of this research is driven by the low level of adoption of AI-based digital technology by MSME players, even though this technology has great potential in increasing promotional effectiveness, consumer engagement, and competitiveness of local products. The method used is a descriptive qualitative approach, with in-depth interview techniques and observation of 10 local MSME players in the tourism sector. The results showed that most MSME players have utilised social media in promotion, but have not optimally integrated AI technology. The main barriers are lack of training, digital literacy, and limited infrastructure. Nonetheless, there is strong interest in AI as a future marketing solution. This research proposes a strategy to strengthen the digital capacity of MSME players through training, community-based mentoring, and collaboration with technology stakeholders. By optimising AI, Sugihen Village MSMEs have the potential to increase consumer engagement, expand markets, and contribute to sustainable local economic growth.